ANALISIS KESULITAN BELAJAR SISWA MATERI IPAS RANGKAIAN LISTRIK KELAS V SDN TLOGOSARI KULON 06 - Frida Nur Asyifa; Reffiane, Fine; Arisyanto, Prasena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the low understanding of fifth-grade students at SDN Tlogosari Kulon 06 Semarang regarding the science subject (IPAS), particularly electrical circuits, which results in poor learning outcomes and difficulties in applying scientific concepts. The literature review references learning difficulty theories covering aspects of perception, concentration, motivation, and the influence of the learning environment on student achievement. This qualitative study employs observation, interviews, and questionnaires as data collection methods, involving teachers, students, and parents as research subjects. The results indicate the primary learning difficulties arise from both internal and external factors. Internal factors include low motivation, lack of interest in IPAS material, varied cognitive abilities among students, and unstructured learning patterns. External factors include the use of conventional teaching methods without interactive approaches, limited supporting facilities at school and home, and weak parental support and supervision, which contribute to students' learning challenges. Based on these findings, it is recommended to provide adequate facilities and implement personalized learning approaches to enhance students' motivation and learning outcomes. Furthermore, continuous guidance from teachers and parents is essential to effectively address students' learning difficulties.